Norovirus - Mitchell, Brett (International Journal of Infection Control, 2009)
Highly infectious agents in a hospital setting can have a significant impact on the functioning of clinical areas, patient delivery and care. Norovirus is one such organism and is now one of the most common causes of gastroenteritis.8 The transmission and identification of this virus will be reviewed with a focus on a hospital setting. Symptoms and management of patients suffering from this virus will also be discussed. During outbreaks of Norovirus, staff are often reservoirs for transmission and often become infected themselves. Therefore it is important that the management of staff, including infection control issues and public health issues, are also analysed. Communication with all members of staff, patients and relatives are paramount in controlling and managing outbreaks.